ECIL guidelines for preventing Pneumocystis jirovecii pneumonia in patients with haematological malignancies and stem cell transplant recipients - Maertens, Johan; Cesaro, Simone; Maschmeyer, Georg; Einsele, Hermann; Donnelly, J. Peter; Alanio, Alexandre; Hauser, Philippe M.; Lagrou, Katrien; Melchers, Willem J. G.; Helweg-Larsen, Jannik; Matos, Olga; Bretagne, Stéphane; et al. (Journal of antimicrobial chemotherapy, 2016)
The 5th European Conference on Infections in Leukaemia (ECIL-5) meeting aimed to establish evidence-based recommendations for the prophylaxis of Pneumocystis jirovecii pneumonia (PCP) in non-HIV-infected patients with an underlying haematological condition, including allogeneic HSCT recipients. Recommendations were based on the grading system of the IDSA. Trimethoprim/sulfamethoxazole given 2–3 times weekly is the drug of choice for the primary prophylaxis of PCP in adults (A-II) and children (A-I) and should be given during the entire period at risk. Recent data indicate that children may benefit equally from a once-weekly regimen (B-II). All other drugs, including pentamidine, atovaquone and dapsone, are considered second-line alternatives when trimethoprim/sulfamethoxazole is poorly tolerated or contraindicated. The main indications of PCP prophylaxis are ALL, allogeneic HSCT, treatment with alemtuzumab, fludarabine/cyclophosphamide/rituximab combinations, >4 weeks of treatment with corticosteroids and well-defined primary immune deficiencies in children. Additional indications are proposed depending on the treatment regimen.